Effectiveness of probiotic, prebiotic, and synbiotic therapies in reducing postoperative complications: A systematic review and network meta-analysis - Nongyao Kasatpibal (2018)
© The Author 2017. Published by Oxford University Press for the Infectious Diseases Society of America. All rights reserved. Background. Microbiome-directed therapies are increasingly used preoperatively and postoperatively to improve posto perative outcomes. Recently, the effectiveness of probiotics, prebiotics, and synbiotics in reducing postoperative complications (POCs) has been questioned. This systematic review aimed to examine and rank the effectiveness of these therapies on POCs in adult surgical patients. Methods. We searched for articles from PubMed, Embase, Cochrane, Web of Science, Scopus, and CINAHL plus. From 2002 to 2015, 31 articles meeting the inclusion criteria were identified in the literature. Risk of bias and heterogeneity were assessed. Network meta-analyses (NMA) were performed using random-effects modeling to obtain estimates for study outcomes. Risk ratios (RRs) and 95% confidence intervals (CIs) were estimated. We then ranked the comparative effects of all regimens with the surface under the cumulative ranking (SUCRA) probabilities. Results. A total of 2,952 patients were included. We found that synbiotic therapy was the best regimen in reducing surgical site infection (SSI) (RR = 0.28; 95% CI, 0.12-0.64) in adult surgical patients. Synbiotic therapy was also the best intervention to reduce pneumonia (RR = 0.28; 95% CI, 0.09-0.90), sepsis (RR = 0.09; 95% CI, 0.01-0.94), hospital stay (mean = 9.66 days, 95% CI, 7.60- 11.72), and duration of antibiotic administration (mean = 5.61 days, 95% CI, 3.19-8.02). No regimen significantly reduced mortality. Conclusions. This network meta-analysis suggests that synbiotic therapy is the first rank to reduce SSI, pneumonia, sepsis, hospital stay, and antibiotic use. Surgeons should consider the use of synbiotics as an adjunctive therapy to prevent POCs among adult surgical patients. Increasing use of synbiotics may help to reduce the use of antibiotics and multidrug resistance.